Children's fears and its relation to parenting style and demographic variables of children and parents. Issue 6 (26th April 2021) - Ahmad, Jamal
ABSTRACT: The purpose of this study was to examine the fears of Jordanian children and how it related to parenting styles and demographics. The study used the quantitative methodology of a survey to examine fears of a sample of 640 Jordanian children aged 4–9 in Al-Zarqa city. Results revealed that the most specific fear was imaginary or animals. The least feared type was loud noises. Results also found that children's fears differ due to the age of the child in favour of younger children. Furthermore, analyses revealed no significant differences due to father's and mother's education level, monthly income, children's birth order, gender or residency. Results also showed a strong positive correlation between mother authoritarian parenting style and children's fears. Based on the findings, younger children and children whose mothers use an authoritarian parenting style are at higher risk of developing fears that can grow into anxiety, phobia, or worry.